2014
DOI: 10.1007/s00383-014-3543-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Clostridium difficile on paediatric surgical practice: a systematic review

Abstract: Severe or complicated CDI in both HD and non HD paediatric patients is associated with high mortality and often requires surgical intervention. Although these patient cohorts represent a small number of cases, CDI should be suspected in children presenting with enterocolitis to enable early diagnosis and timely surgical intervention, particularly in patients with co-morbid conditions or preceding antibiotic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 94 publications
0
5
0
3
Order By: Relevance
“…Weiterhin findet sich eine CDI signifikant häufiger bei Patienten mit onkologischen Erkrankungen, nach Stammzelltransplantation oder solider Organtransplantation [59,60]. Zusätzlich gibt es Fallberichte zu schweren Verläufen einer CDI bei Patienten mit Mukoviszidose [65,66] und bei Morbus Hirschsprung [67].…”
Section: I31 Statementunclassified
See 1 more Smart Citation
“…Weiterhin findet sich eine CDI signifikant häufiger bei Patienten mit onkologischen Erkrankungen, nach Stammzelltransplantation oder solider Organtransplantation [59,60]. Zusätzlich gibt es Fallberichte zu schweren Verläufen einer CDI bei Patienten mit Mukoviszidose [65,66] und bei Morbus Hirschsprung [67].…”
Section: I31 Statementunclassified
“…Entscheidende Determinante für den Nachweis von Clostridien im Darm von Frühgeborenen ist die Zeitdauer des Aufenthalts auf der Intensivstation[97]. Trotz der hohen Rate asymptomatischer Träger von C. difficile bei Säuglingen kann C. difficile eine Ursache für eine besonders schwer verlaufende Kolitis bei M. Hirschsprung sein[67].Exazerbationen chronisch-entzündlicher Darmerkrankungen sind auch im Kindesalter mit CDI assoziiert[64,[98][99][100].Tests auf C. difficile sollten nur bei symptomatischen Patienten mit klinisch signifikanten wässrigen Durchfällen erfolgen, wenn es Verdacht auf eine CDI gibt oder prädisponierende Faktoren dafür vorliegen. Bei Säuglingen sollten Tests auf C. diff.…”
unclassified
“…[ 18] There was insufficient data to analyze the role of other pathogens. One retrospective study found 58% of patients with HAEC had a cow's milk allergy.…”
Section: Infectionmentioning
confidence: 99%
“…Thus, refractory constipation may be associated with future risk of C. difficile toxic megacolon. 1 More than 90% of patients with C. difficile infection clinically present with watery or bloody diarrhoea 2. To our knowledge, there is only one case report of an adult patient with C. difficile infection who presented with constipation 3…”
Section: Descriptionmentioning
confidence: 99%